Shear banding in drying films of colloidal nanoparticles - Yang, Bin; Sharp, James S.; Smith, Michael I. (American Chemical Society, 2015)
Drying suspensions of colloidal nanoparticles exhibit a variety of interesting strain release mechanisms during film formation. These result in the selection of characteristic length scales during failure processes such as cracking and subsequent delamination. A wide range of materials (e.g., bulk metallic glasses) release strain through plastic deformations which occur in a narrow band of material known as a shear band. Here we show that drying colloidal films also exhibit shear banding. Bands are observed to form a small distance behind the drying front and then to propagate rapidly at ∼45 to the direction of drying. It is shown that the spacing of the bands depends on salt concentration and the evaporation rate of the colloidal suspension. These combined observations suggest that there is a critical shear rate (related to the film yield stress) which controls the ratio of bandwidth to band spacing. Local deformations were measured in the early stages of drying using fluorescent tracer particles. The measurements were used to show that the existence of shear bands is linked to the compaction of particles perpendicular to the drying front. The spacing of shear bands was also found to be strongly correlated with the characteristic length scale of the compaction process. These combined studies elucidate the role of plastic deformation during pattern formation in drying films of colloidal nanoparticles.